Increased corticosterone levels in mice subjected to the rat exposure test - Santana Amaral, Vanessa Cristiane [UNESP]; Gomes, Karina Santos [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
In recent years, there has been a notable interest in studying prey-predator relationships to develop rodent-based models for the neurobehavioral aspects of stress and emotion. However, despite the growing use of transgenic mice and results showing important differences in the behavioral responses of rats and mice, little research has been conducted regarding the responses of mice to predators. The rat exposure test (RET), a recently developed and behaviorally validated prey-predator (mouse-rat)-based model, has proven to be a useful tool in evaluating the defensive responses of mice facing rats. To further validate the RET, we investigated the endocrine and behavioral responses of mice exposed to this apparatus. We first constructed a plasma corticosterone secretion curve in mice exposed to a rat or to an empty cage (control). Rat-exposed mice showed a pronounced rise in corticosterone levels that peaked 15 min from the beginning of the predator exposure. The corticosterone levels and behavioral responses of mice exposed to a rat or to a toy in the RET apparatus were then measured. We observed high plasma corticosterone levels along with clear avoidance behaviors represented by decreases in tunnel and surface area exploration and increases in risk assessment behaviors and freezing. This strongly suggests that the test elicits a repertoire of behavioral responses compatible with an aversion state and indicates that it is a promising model for the evaluation of prey-predator interactions. However, more physiological, neurochemical, and pharmacological studies are needed to further validate the test. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Mouse; Rat exposure test; Prey-predator interaction; Corticosterone; Anxiety; Defensive behavior; Risk assessment